Biosimilars: when value meets cost - de Mora, Fernando (Henry Stewart Talks, 2023)
Biologic versus Non-biologic medicines, Biosimilars development: milestones, Original-to-biosimilar interchangeability, Impact of biosimilars on access to biologics, A value proposition for biosimilars